2021
DOI: 10.13189/ujph.2021.090617
|View full text |Cite
|
Sign up to set email alerts
|

Association between Breastfeeding and Child Stunting among Adolescent Mothers

Abstract: Introduction: Child stunting is one of the global public health problems and breastfeeding is one of the modifiable maternal factors protecting against child stunting. The current study aims to determine the prevalence of breastfeeding and its association with child stunting among adolescent mothers. Methods: A cross-sectional study was conducted in Phra Nakhon Si Ayutthaya province. Using multi-stage stratified sampling method, 250 participants were recruited. Data were collected using structured interview qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Adapun upaya untuk mencegah dan mengurangi pengerdilan anak harus mencakup sistem pengawasan stunting dan kampanye pola makan sehat dan dasar teknik untuk gaya hidup sehat di antara kelompok risiko harus didirikan bersama dengan program berbagi pengetahuan tentang faktor-faktor yang berhubungan dengan stunting (Chaveepojnkamjorn et al, 2021). Pendapatan keluarga, pengasuh, kunjungan ke posyandu, dan pemberian makanan tambahan juga berperan dalam kejadian stunting.…”
Section: Discussionunclassified
“…Adapun upaya untuk mencegah dan mengurangi pengerdilan anak harus mencakup sistem pengawasan stunting dan kampanye pola makan sehat dan dasar teknik untuk gaya hidup sehat di antara kelompok risiko harus didirikan bersama dengan program berbagi pengetahuan tentang faktor-faktor yang berhubungan dengan stunting (Chaveepojnkamjorn et al, 2021). Pendapatan keluarga, pengasuh, kunjungan ke posyandu, dan pemberian makanan tambahan juga berperan dalam kejadian stunting.…”
Section: Discussionunclassified
“…Implementation of health literacy and prevention programs is important in children's health care [19]. Educating parents through audiovisual programs and pamphlets focusing on the harmful effects of lead can be effective for children with elevated blood lead levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…Stunting is an essential indicator of long-term chronic undernutrition since this reflects a failure to achieve linear growth due to prolonged food insecurity and illnesses in childhood (Tamrat et al, 2020). Stunting is the most common form of child malnutrition and one of the world's fundamental health problems; characterized by a height-to-age ratio deficit that causes delayed development, impaired cognitive function, and increased susceptibility to infectious diseases in children (Chaveepojnkamjorn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In one study in Thailand, teenage pregnancies were associated with stunting in children due to mothers' youth and lack of maturity and nutritional knowledge to care for their children. Furthermore, many had unplanned pregnancies and may not have been aware of their food consumption before becoming pregnant (Chaveepojnkamjorn et al, 2021). One study review explained framework determinants and identified five broad groups of factors linking adolescent mothers to child undernutrition, including maternal nutritional status, education and bargaining power, access to health services, child feeding practice, and living conditions (Nguyen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%